Epithelioid hemangioma in the oral cavity: Report of a rare case - Fabiana Nunes de Assis; Natanael Henrique Ribeiro Mattos; Cintia Mussi Milani (Sociedade Portuguesa de Estomatologia e Medicina Dentária, 2022)
The epithelioid hemangioma (EH), also known as angiolymphoid hyperplasia with eosinophilia, is a benign, neoplastic vascular tumor rarely presented in the mouth. It is most frequent in young adult male patients. Clinically, it is characterized by papules or nodules, usually with a reddish-brown color, mimicking other vascular and non-vascular lesions. Histologically, the lesion is composed of well-formed round vessels with epithelioid endothelial cells, with a histiocytoid appearance, surrounded by an infiltrate of lymphocytes and eosinophils. Oral EH's endothelial cells are commonly immunoreactive for CD34 and factor VIII antigen. Surgical excision is the most widely used form of treatment, and recurrences are uncommon. The aim of this study was to report a rare case of oral EH in a 52-year-old female patient.